PENERAPAN MODEL PEMBELAJARAN GUIEDE, ORGANIZING, LEAFLET, DISCOVERY (GOLD) UNTUK MENINGKATKAN PROSES BELAJAR MATEMATIKA SISWA KELAS V UPT SD NEGERI 4 WANIO KABUPATEN SIDRAP - Hasan, Kamaruddin; Maryam, St.; Bakri, Helmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research (CAR) focuses on the learning outcomes of fifth-grade students at UPT SD Negeri 4 Wanio. This research is qualitative with data collection techniques including observation and documentation. The subjects of this research are 11 students and 1 teacher. The research was conducted in 2 cycles. In cycle I, the teacher's activity was classified as Poor (K), the students' activity was classified as Fair (C), and the evaluation results received a classification of Poor (K). In the implementation of cycle II, the teacher's activity was classified as Good (B), the students' activity was classified as Good (B), and the evaluation test results received a classification of Good (B). Therefore, the conclusion of this research is that applying the GOLD learning model can improve the learning process and outcomes of students in the data presentation material in fifth grade at UPT SD Negeri 4 Wanio, Sidrap Regency.